Strategic Management / The Challenge of Creating Value Second Edition - Fitzroy Peter; Ghobadian Abby; Hulbert James M (Rouledge, 2012)
This textbook provides an integrated theoretical and practical approach to strategic management for value creation. Strategic Management Concepts, Managing Strategically, Strategic Management Fundamentals, Strategic Analysis, External Analysis: The Business Environment, External Analysis: The financial Environment, Internal Analysis: Managing Capabilities and Costs and Knowledge, Strategic Development, Creating Future Direction, Business-level Strategy, Corporate-level Strategy, Managing Innovation and the Dynamic Scope of the Firm, Strategy Implementation, Leading Organizational Change, Designing Organizational Architecture, Assessing Strategic Performance, Measuring Organizational Performance, Corporate Governance and Social Responsibility, Postscript.